Behaviour of Hollow Steel Structural Elements – Bare or retrofitted - Narayanan, S.P; Kalaikumar, V.; Cossa, N.J.; Hasifi, M.S.; Razak, A.A. (2010)
Steel tubular members are either compression or beam elements used in high rise buildings, industrial structures, piles, bridge piers and offshore structures. They are used either as bare sections, or infilled with concrete or grout or retrofitted using cfrp. Infilling or retrofitting is a sustainable option compared to replacement as it more economical and extends the life of the structure. The behaviour of short length steel tubular – bare or infilled with normal concrete – is widely reported. The codes provide expressions for evaluating the nominal strength of short and long, bare and infilled steel columns. Not many studies on intermediate length steel columns are reported. The ongoing research on concrete infilled steel tubular sections studied the following two aspects: (1) Short or intermediate length steel tubulars with slenderness below 200, infilled with concrete of grades 30, 60 and 80 N/mm2 tested in axial compression and comparison with the code predicted ultimate strengths using EC4and BS5400. (2) Beams of 1m span using bare hollow sections or infilled with concrete and grout or retrofitted using CFRP. The experimental results are compared with ultimate values calculated using the basic stress –strain block theory. The behaviour of the column and beam under loading is discussed using the stress strain plots.